1992
DOI: 10.1044/1058-0360.0102.44
|View full text |Cite
|
Sign up to set email alerts
|

The Quality of Life of Young Adults With Histories of Specific Language Impairment

Abstract: When a child is diagnosed as having a language disorder, parents may ask the speech-language pathologist questions such as "How might this language disorder affect my child’s life?" Unfortunately, professionals have little empirical information upon which to base an answer to this question. The purpose of this paper is to provide information regarding reported quality of life (QOL) for a group of young adults with histories of mild to severe specific language impairment who had received language treatment. A Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
63
2

Year Published

1997
1997
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(76 citation statements)
references
References 28 publications
11
63
2
Order By: Relevance
“…Records, Tomblin, and Freese (1992) reported that young adults with SLI had significantly lower income levels than controls without such history. Under the assumption that the children diagnosed in this study have the same liabilities, we must conclude that due to the sizable prevalence rate of SLI and its associated morbidity, there is a considerable aggregate cost to the quality of life of our nation's children and to the economic productivity of its citizens.…”
Section: Discussionmentioning
confidence: 99%
“…Records, Tomblin, and Freese (1992) reported that young adults with SLI had significantly lower income levels than controls without such history. Under the assumption that the children diagnosed in this study have the same liabilities, we must conclude that due to the sizable prevalence rate of SLI and its associated morbidity, there is a considerable aggregate cost to the quality of life of our nation's children and to the economic productivity of its citizens.…”
Section: Discussionmentioning
confidence: 99%
“…One study reported significant differences compared to peers in some aspects of HRQoL, such as speech, mental functioning, usual activities, and distress . In contrast, and Records, Tomblin, and Freese (1992) reported no differences in HRQoL between adults with and without histories of SLI, despite evidence in both studies of participants' continued language impairment in adulthood. Observed differences may stem from variations across participant groups; for example, most adults in the study by Arkkila and colleagues had severe language disorders as children, whereas in other studies level of severity was not reported.…”
Section: Adult Studiesmentioning
confidence: 60%
“…One study has reported significant differences compared to peers, in some aspects of HRQoL particularly for speech, mental functioning, usual activities, and distress (Arkilla, Räsänen, Roine, Sintonen, & Vilkman, 2008a). In contrast, and Records, Tomblin, and Freese (1992) reported no differences in HRQoL between adults aged 17-25 years with (n = 29) and without (n = 29) 31 histories of SLI, despite evidence in both studies of continued language impairment in adulthood. There has also been considerable research examining the HRQoL of people who have had laryngectomies.…”
Section: Adult Studiesmentioning
confidence: 81%
See 1 more Smart Citation
“…By contrast, quality of life (QoL) research in developmental medicine has been rare. Records et al [8] investigated the QoL of 29 young adults with a history of SLI and 29 controls. Subjects were aged 17-25 years.…”
Section: Introductionmentioning
confidence: 99%